2018
DOI: 10.1017/s0950268818000961
|View full text |Cite
|
Sign up to set email alerts
|

Age bias in survey sampling and implications for estimating HIV prevalence in men who have sex with men: insights from mathematical modelling

Abstract: Respondent-driven sampling (RDS) is widely used to estimate HIV prevalence in men who have sex with men (MSM). Mathematical models that are calibrated to these data may be compromised if they fail to account for selection biases in RDS surveys. To quantify the potential extent of this bias, an agent-based model of HIV in South Africa was calibrated to HIV prevalence and sexual behaviour data from South African studies of MSM, first reweighting the modelled MSM population to match the younger age profile of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Of the men who are gay or bisexual, 77% are assumed to be in the bisexual category. This estimate is the average of the 100 best-fitting parameters obtained when the model was previously fitted to South African sexual behaviour data from MSM [160]. The data are from respondent-driven sampling (RDS) studies, in which the proportion of MSM who reported having ever had sex with women varied between 36% and 87% (average value of 58%) [131, 135, 161163].…”
Section: Sexual Behaviourmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the men who are gay or bisexual, 77% are assumed to be in the bisexual category. This estimate is the average of the 100 best-fitting parameters obtained when the model was previously fitted to South African sexual behaviour data from MSM [160]. The data are from respondent-driven sampling (RDS) studies, in which the proportion of MSM who reported having ever had sex with women varied between 36% and 87% (average value of 58%) [131, 135, 161163].…”
Section: Sexual Behaviourmentioning
confidence: 99%
“…To reflect this heterogeneity, we sample the a i values from a beta distribution with mean 0.23 and standard deviation 0.09 and sample the b i values from a normal distribution with mean - 0.015 and standard deviation 0.16. As before, each parameter estimate is calculated as the average of the 100 best-fitting parameters obtained when the model was previously fitted to South African sexual behaviour data from MSM [160]. The model thus suggests that men in the bisexual category tend to have more female partners than male partners, and that there is a slight tendency towards relatively more female partners as men get older (although with substantial variation between individuals).…”
Section: Sexual Behaviourmentioning
confidence: 99%
See 3 more Smart Citations